The effect of exogenous NO on PSI photochemistry in intact pea leaves - Wodala, Barnabás; Horváth, Ferenc (Acta Biologica Szegediensis, 2008)
We investigated the effect of exogenous NO on PSI photochemistry by measuring P700 absorbance changes at 810-870 nm in intact pea leaves treated with the NO donor GSNO. Our results indicate that NO increases PSI quantum efficiency and the pool size of electrons in the intersystem chain.